2007
DOI: 10.1007/s00442-007-0831-y
|View full text |Cite
|
Sign up to set email alerts
|

Test of local adaptation to biotic interactions and soil abiotic conditions in the ant-tended Chamaecrista fasciculata (Fabaceae)

Abstract: Few previous studies have assessed the role of herbivores and the third trophic level in the evolution of local adaptation in plants. The overall objectives of this study were to determine (1) whether local adaptation is present in the ant-defended plant, Chamaecrista fasciculata, and (2) the contribution of ant-plant-herbivore interactions and soil source to such adaptation. We used three C. fasciculata populations and performed both a field and a greenhouse experiment. The first involved reciprocally transpl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 70 publications
3
25
0
Order By: Relevance
“…Despite environmental differences and the low probability of genetic exchange between our populations, the scale chosen for the reciprocal transplant experiment was possibly too small to detect local adaptation. This hypothesis is in line with results of studies on another annual species of disturbed habitats, Chamaecrista fasciculata, which showed local adaptation only at distances of [100 km (Galloway and Fenster 2000;Abdala-Roberts and Marquis 2007). However, a full reciprocal design would be required to verify whether Brassica nigra is locally adapted at larger scales.…”
Section: Local Adaptation Of Plants and Herbivoressupporting
confidence: 79%
“…Despite environmental differences and the low probability of genetic exchange between our populations, the scale chosen for the reciprocal transplant experiment was possibly too small to detect local adaptation. This hypothesis is in line with results of studies on another annual species of disturbed habitats, Chamaecrista fasciculata, which showed local adaptation only at distances of [100 km (Galloway and Fenster 2000;Abdala-Roberts and Marquis 2007). However, a full reciprocal design would be required to verify whether Brassica nigra is locally adapted at larger scales.…”
Section: Local Adaptation Of Plants and Herbivoressupporting
confidence: 79%
“…There are numerous examples from the literature that show that the edaphic composition has a strong impact on plant fitness (Stratton 1994;Hangelbroek et al 2003;Abdala-Roberts and Marquis 2007) and its effect may vary spatially leading in some cases to local adaptation, which is a superior fitness of local populations to their home conditions in comparison to non-local populations (Antonovics 1971;Brandon and Antonovics 1996;Linhart and Grant 1996;Joshi et al 2001). However, whether interactions between plant and soil biota are able to exhibit variation across sites resulting in population differentiation and local adaptation has only been addressed on a few occasions (Van der Putten et al 2006;Macel et al 2007;Hoeksema and Thompson 2007;Piculell et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Based on these results, it has been often assumed that plant local adaptation is a common condition across populations and species. Nevertheless, several studies have found no evidence for local adaptation in plants (e.g., Platenkamp 1990, Leiss andMuller-Scharer 2001;Abdala-Roberts and Marquis 2007;Ortegón-Campos et al 2009), and a recent metaanalysis suggests that local adaptation is less common than previously thought (Leimu and Fischer 2008), thus questioning the ubiquity of the phenomenon.…”
Section: Introductionmentioning
confidence: 95%
“…However, during the last decade there has been an increase in the number of investigations which have addressed the degree to which plants are locally adapted to biotic factors such as insect herbivores (Sork et al 1993;Abdala-Roberts and Marquis 2007;Ortegón-Campos et al 2009), pathogens (e.g., Crémieux et al 2008, mutualists (AbdalaRoberts and Marquis 2007; Gómez et al 2009), as well as the influence competition has on local adaptation (e.g., Sambatti and Rice 2006). The most powerful approach to measure the contribution of biotic (or abiotic) factors to plant local adaptation is to perform reciprocal transplants while simultenously manipulating the abundance or effect of the biotic counterpart (i.e., herbivore, pollinator, competitor; Nuismer and Gandon 2008).…”
Section: Introductionmentioning
confidence: 99%